Violation of Accountant Professional Ethics in the Case of PT. Indofarma Tbk - Devi Savira S; Sri Trisnaningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The code of professional ethics is an important rule for a profession that aims to improve quality and maintain the dignity of the profession. Where an accountant must uphold ethical principles so as to build trust for users of accounting services. The many business competitions that occur today, give rise to violations of professional ethics. This violation is a very serious problem for the ethical standards of the accounting profession, one of which was found in violations at PT Indofarma Tbk which engineered its financial statements. By creating receivables, payables, and down payments for the purchase of fictitious medical devices, so that it seemed as if the company's target had been achieved. This case study review will later end with recommendations that are in line with the company's expectation.